Analysis of Latin American research in the field of communication and public opinion - Lotero-Echeverri, Gabriel (2020)
We analyzed papers published by researchers from Latin American and from Spain and Portugal (Ibero-America) in the last three years, in the field of public opinion. This study identified topics of interest and principal research techniques. We used qualitative analysis program NVivo11 in the analysis of the findings. As a result, it can be highlighted the predominance of investigation on digital communication, centrally on the digital social network, particularly on Twitter.